The Role of Fathers in Gender Recognition among Early Childhood: A Literature Review on Gender Bias Contexts - Berta Laili Khasanah; Salma Aulia Khosibah; Afifah Rahmaningrum (PG PAUD Universitas Negeri Surabaya, 2025)
This study explores the role of fathers in fostering gender recognition in early childhood within the context of gender bias. Using a Systematic Literature Review (SLR) with a PRISMA-based approach, four stages were conducted: identification, screening, eligibility, and inclusion. Articles were collected from Google Scholar, Science Direct, and Scispace using keywords related to fathering patterns, gender introduction, and early childhood care. From 7,750 initial results, filtering by publication year 2022–2025, topic relevance, and inclusion criteria produced 10 core articles for analysis. The findings reveal that fathers’ roles have shifted from traditional breadwinners to multidimensional figures educators, protectors, co-parents, and role models. Active and empathetic father involvement supports flexible gender identity development through play, communication, and emotional interaction. Factors such as education, culture, working hours, and communication style influence this role. The study highlights the importance of father engagement in promoting inclusive and unbiased gender understanding from early childhood.